2018
DOI: 10.1371/journal.pone.0194272
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour during transportation predicts stress response and lower airway contamination in horses

Abstract: This study aimed to document the effects of an eight hour journey on behavioural, clinical, haematological, environmental and respiratory parameters, and to identify possible associations between factors. Twelve horses underwent clinical examination, respiratory endoscopy with tracheal wash (TW) aspiration, and collection of venous and arterial blood before (BJ) and after the journey (AJ). TW were submitted for conventional quantitative bacteriological evaluation and genetic microbiome analyses. Behaviour was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 56 publications
0
57
0
Order By: Relevance
“…In part 1, a preliminary study was conducted in which horses were subjected to confinement, sampling and gastroscopy procedures that mimicked those experienced during transportation. Transported horses had well‐characterized clinical, hematological, and blood biochemistry changes reported after transportation in previous studies, and these changes were not observed in horses confined for a similar duration. Plasma cortisol concentrations increased in transported horses, as has been reported previously .…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In part 1, a preliminary study was conducted in which horses were subjected to confinement, sampling and gastroscopy procedures that mimicked those experienced during transportation. Transported horses had well‐characterized clinical, hematological, and blood biochemistry changes reported after transportation in previous studies, and these changes were not observed in horses confined for a similar duration. Plasma cortisol concentrations increased in transported horses, as has been reported previously .…”
Section: Discussionmentioning
confidence: 78%
“…Transportation is associated with factors that may contribute to gastric ulceration such as physiologic stress responses (increased heart rate and serum cortisol concentrations), changes in feeding practices and water consumption, and changes in GI microbiota . Our study was conducted to determine the impact of 12 hours of transportation without food or water on gastric ulcer scores and gastric fluid (GF) pH in horses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transportation has been identified as a stressor for horses, and has been associated with several adverse outcomes including injury, respiratory and gastrointestinal disease [1][2][3][4][5][6]. We have recently shown that 12 hours' transportation is associated with ulceration of the gastric squamous mucosa in fasted horses, associated with increased pH of gastric content, and possibly with decreased gastrointestinal motility in horses fed 1 h and 6 h prior to transportation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome has a multifactorial etiology, including infectious agents, host and environmental factors, with particular emphasis on transport stress. The latter is indeed responsible for physiological changes that favor pathogen proliferation and invasion of tissues by opportunistic pathogens [1][2][3][4][5]. Viruses and stress-related behavior interfere with the mucociliary clearance of the respiratory tract and dysregulate the tracheal antimicrobial peptides of the innate defenses, allowing opportunistic bacteria to cause pulmonary infections [2,6].…”
Section: Introductionmentioning
confidence: 99%